Bad phosphorylation as a target of inhibition in oncology. (28th February 2018) - Bui, Ngoc-Linh-Chi; Pandey, Vijay; Zhu, Tao; Ma, Lan; Basappa,; Lobie, Peter E.
Abstract: Bcl-2 agonist of cell death (BAD) is a BH3-only member of the Bcl-2 family which possesses important regulatory function in apoptosis. BAD has also been shown to possess many non-apoptotic functions closely linked to cancer including regulation of glycolysis, autophagy, cell cycle progression and immune system development. Interestingly, BAD can be either pro-apoptotic or pro-survival depending on the phosphorylation state of three specific serine residues (human S75, S99 and S118). Expression of BAD and BAD phosphorylation patterns have been shown to influence tumor initiation and progression and play a predictive role in disease prognosis, drug response and chemosensitivity in various cancers. This review aims to summarize the current evidence on the functional role of BAD phosphorylation in human cancer and evaluate the potential utility of modulating BAD phosphorylation in cancer. Highlights: BAD has pro-apoptosis and pro-survival functions involved in cancer development. BAD is phosphorylated by kinases that are linked to cancer cell survival pathways. Phosphorylation of BAD were shown to promote survival and drug resistance in cancer. Abrogating BAD phosphorylation by kinase inhibitors have shown limited success. Novel strategies to target BAD phosphorylation need to be developed.